Harvest - Manjula Padmanabhan (Hachette, 2017)
A modern morality play. A bitter, savagely funny vision of the cannibalistic future that awaits the human race...’ – OUTLOOK A searing portrayal of a society bereft of moral and spiritual anchors, Manjula Padmanabhan’s fifth play, Harvest, won the Onassis Award for Original Theatrical Drama in 1997, the first year in which the prize was awarded. Following its international premiere in Greece in 1999, the play has been performed over the years by theatre groups, both amateur and professional, around the world. A dark satire, Harvest tells the story of an impoverished family and the Faustian contract they enter into with a shadowy international corporation: fabulous wealth in exchange for the organs of one of its members. As Ginni, the glamorous American woman who hopes to receive the organs, invades their one-room home via an interactive video device the play lays bare the transactional nature of human relationships – even the most intimate ones. This edition includes, for the first time, a gender-reversed version of the play – an experiment by the author that provides startling insight into the stereotypes and societal constructs ingrained deep in the human psyche and, indeed, into how we perceive gender.